Biotin-Thiamine-Responsive Basal Ganglia Disease: A Case Report - Jonathan Tse; Asem Abu-Qamar; Omar Youssef; Sherry L. Pejka (Case Reports in Neurology)
Introduction: Biotin-thiamine responsive basal ganglia disease (BTBGD) is a rare autosomal recessive neurometabolic disorder characterized by diverse and variable phenotypic features, which can make diagnosis challenging. However, prompt treatment with thiamine and biotin can effectively manage the condition. Diagnosis relies on the identification of biallelic pathogenic variants in the SLC19A3 gene. This case report describes two novel variants of uncertain significance in the SLC19A3 gene, which may be correlated with the phenotypic manifestations of BTBGD. Case Presentation: Our case is a 7-month-old female infant who presented with a 3-week history of irritability, altered behavior, and refusal of newly introduced solid foods. Symptoms started with an upper respiratory tract infection, followed by lethargy, floppiness, and abnormal movements. The patient was admitted to the pediatric ward with a broad differential diagnosis. Extensive laboratory evaluations revealed lactic acidosis. MRI brain showed symmetric restricted diffusion affecting the bilateral basal ganglia, thalami, and cortical regions. Whole genome sequencing identified biallelic variants of the SLC19A3: a c.1364T>G p.Met455Arg missense variant in the maternal allele and a 2.3 kb deletion of intron 3 of the paternal allele. Both variants were identified as variants of uncertain significance. However, given the clinical picture, MRI brain findings, resolution of symptoms with empiric biotin and thiamine supplementation, and biallelic SLC19A3 variants of unknown significance, the patient most likely suffers from BTBGD. Patient continues to show sustained developmental progress on biotin and thiamine supplementation. Conclusion: This case highlights the fact that genetic testing remains a vital but improvable tool for the diagnosis of BTBGD. As of yet, genetic testing and diagnosis of BTBGD continues to be limited by the knowledge of which SLC19A3 variants are established to be pathogenic variants. Thus, further research is required to study other SCL19A3 variants of unknown significance to further improve genetic testing and diagnosis of BTBGD in the future.